The Determinants Of Innovative Behavior Among Early Childhood Educators In Guangdong: The Mediating Role Of Self Efficacy - Tang, Xuan (2024)
This study focused on investigating the factors influencing innovative behavior among educators through the mediating role of self-efficacy in early childhood education in Guangdong, China, through the dual lens of social cognitive theory and social exchange theory. Using a quantitative research approach, data were collected from 476 educators through a questionnaire survey-based method. The primary independent variables investigated include focused instruction, professional community, instructional leadership, shared leadership, and trust in the principal. Innovative behavior functioned as the dependent variable, while educators’ selfefficacy was positioned as the mediating variable. The findings demonstrate significant positive associations between the independent variables and the educators’ self-efficacy, as well as between the educators’ self-efficacy and their innovative behavior. Crucially, self-efficacy emerged as a potent mediator in the relationship between the designated independent variables and innovative behavior. These results highlight the instrumental role that self-efficacy plays in fortifying educators’ innovative capacities in early childhood education. Drawing on these empirical discoveries, this research introduces the innovation and efficacy training model as a recommendation for educators, including those factors explored by this study.